Z problematyki winy nieumyślnej jednostki gospodarki nieuspołecznionej - Napierała, Jacek (Wydział Prawa i Administracji UAM, 1984)
A study of main theses of the resolution 1' 84 of the Council of State Economic Arbitration setting general guidelines for arbitration decisions in question of debtor's liability in the relations among the units of socialized economy is a subject of the article. The resolution was passed in the relation to changes in economic legislation establishing framework for functioning of the economic reform. Rules of contractual liability elaborated by arbitration (decisions on the grounds of the previous resolution departed both from a classical principle of guilt and from a principle of risk. In any case it was the liability surpassing limits set by art. 355 par. 2 of the Civil Code. A question can be raised whether, and if yes then in which direction change in interpretation in liability rules occurend as compared to the interpretation adopted in the resolution 258. It can be stated by and large that arbitration returned to the rule of art. 355 par. 2 of the C.C. The working „utmost diligence" was omitted and so was the statement that an event excluding debtor from liability must be of external origin. Besides, the resolution under study uses the term of unintentional guilt on describing a notion" of non observation of a due dilligence". But can we state the „return" of the principle of guilt in the relations between the socialized units of economy? It seems that the answer should be negative. There are convincing arguments that the use of a „guilt" notion in Case of a unit of economy is not justified on appraising its acting or desistance. If that notion is however used as a handy epitome, it appears that the most characteristic feature of that legal category (subjective element of guilt) is altogether omitted on appraising acts of those units. It can be therefore inferred that contractual liability in relations between units of economy is of an objective character. The same can also be related to other legislations of economic law where a controversy on „subjective" or „objective" character of the interpretation of liability provisions is actually a dispute on a hierarchy of functions ascribed to those provisions.
On the problems of unintentional guilt of unit of socialized economy